Effect of a Digital Health Exercise Program on the Intention for Spinal Surgery in Adult Spinal Deformity: Exploratory Cross-Sectional Survey - Marsalis Christian Brown; Christopher Quincy Lin; Christopher Jin; Matthew Rohde; Brett Rocos; Jonathan Belding; Barrett I Woods; Stacey J Ackerman (JMIR Formative Research)
Abstract BackgroundAdult spinal deformity (ASD) is a prevalent condition estimated at 38%. Symptomatic ASD is associated with substantial health care costs. The role of nonoperative interventions in the management of ASD remains elusive. The National Scoliosis Clinic’s (NSC) scoliosis realignment therapy (SRT) is a personalized digital health exercise program for the nonoperative management of ASD. ObjectiveThis exploratory study had two objectives: (1) to evaluate the effect of the SRT program on users’ intention of having spinal fusion; and (2) from a US payer perspective, to estimate the annual cost savings per 100,000 beneficiaries by averting spinal surgery. MethodsIndividuals were enrolled in the SRT study from October 1, 2023 to September 1, 2024. Participants completed a web-based, cross-sectional survey about their history of prior scoliosis surgery and intent of having surgery before and after use of SRT (on a 4-point Likert scale, where 1 = “No Intent for Surgery” and 4 = “High Intent for Surgery”). Intent for surgery before and after participation in SRT was compared using a nonparametric Wilcoxon signed-rank test for paired data. Annual cost savings per 100,000 beneficiaries by averting spinal fusions were estimated separately for commercial payers and Medicare using published literature and public data sources. Payer expenditures were inflation-adjusted to 2024 US dollars using the Hospital Services component of the Consumer Price Index. ResultsA total of 62 NSC members (38.8%) responded to the survey and were enrolled in the SRT program for an average (SD) of 17 (12) weeks. The mean (SD) age was 65.3 (13.5) years, and the majority were female (47/48, 98%) and White (45/46, 98%). Among the SRT users who did not have prior scoliosis surgery (n=56), 14% (8/56) reported a decrease in intent for surgery (that is, a lower Likert score) with the use of SRT. The mean (SD) intent for surgery scores before compared to after SRT were 1.29 (0.53) and 1.14 (0.35), respectively (mean difference 0.15 [P ConclusionsSRT is a personalized, scoliosis-specific digital health exercise program with the potential for averting 1 spinal surgery for every 9 participants, resulting in a substantial reduction in payer expenditures while improving the quality of care for commercial payers and Medicare beneficiaries.